Amisulpiride induced tardive dyskinesia: a case report - Chaudhari, Dhananjay; Shanker, Ganesh; Gupta, Kunjan (International Journal of Research in Medical Sciences, 2018)
Amisulpride is a bezamide group of antipsychotic, and like other antipsychotics, it acts by reducing signalling via the dopamine D2 receptor. It is associated with a high risk, of developing increased blood levels of the lactation hormone, prolactin and low risk, as compared with typical antipsychotics, of causing movement disorders. Tardive dyskinesia is a type of movement disorder, which is more common with typical antipsychotics but development of tardive dyskinesia is not rare with the use of atypical antipsychotics. Newer molecules are being developed to reduce the incidence of various dyskinesias, but side effects are evident even with relatively newer molecules. Amisupride is also classed with newer generation of atypical antipsychotic, used to treat schizophrenia and dysthymia. We are reporting a case of middle aged female patient suffering from schizophrenia who developed tardive dyskinesia with the use of amisulpride.